Qualidade do sono e hábitos alimentares em mulheres trabalhadoras em turno em indústria no Sul do Brasil - Martinez, Tauana Antunes (My University, 2024)
Objective: to evaluate the relationship between sleep quality and eating habits in women who work shifts in an industry in southern Brazil. Methods: Cross-sectional study with shift workers at a plastics industry in southern Brazil. The primary stage of the research was eating habits (number of daily meals, consumption of lean meats, addition of salt to ready-made preparations, healthy habits, consumption of organic foods, consumption of snacks throughout the day, consumption of foods without chicken skin, no consumption of fried foods) and the main exposure to sleep quality, being assessed using the PSQI (Pittsburgh Sleep Quality Index) questionnaire. Results: The prevalence of healthy eating habits (> 4) was 64.2%, showing that the majority of workers are able to improve their eating habits, achieving better quality of life and health. In terms of hours of sleep, 34.8% sleep <6 hours and 64.9% sleep ≥ 6. Hours of sleep ≥ 6 and sleep quality showed statistical significance, with 66.9% and 77.8% respectively. Conclusion: Shift work affects the quality and hours of sleep, consequently altering the circadian rhythm and eating habits due to changes in workers' routines. Suggest health education actions to make shift work compatible with quality of life. [resumo fornecido pelo autor]
Objetivo: avaliar a relação entre a qualidade do sono e hábito alimentar em mulheres que trabalham em turnos em uma indústria do Sul do Brasil. Métodos: Estudo transversal com trabalhadoras em turno de uma indústria de plástico do Sul do Brasil. A pesquisa teve como desfecho primário o hábito alimentar (número de refeições por dia, consumo de carnes sem gordura, adição de sal na preparação pronta, hábito saudável, consumo de alimentos orgânicos, hábito de beliscar ao longo do dia, consumo de frango sem pele, não consumo de fritura) e a exposição principal a qualidade do sono, sendo avaliada através do questionário PSQI (Índice de Qualidade do Sono de Pittsburgh). Resultados: Prevalência de hábito alimentar saudável (> de 4) foi de 64,2%, mostrando que boa parte das trabalhadoras podem melhorar seus hábitos alimentares, obtendo maior qualidade de vida e saúde. No quesito horas de sono, 34,8% dormem <6 horas e 64,9% dormem ≥ 6. As horas de sono ≥ 6 e a qualidade do sono apresentaram significância estatística, tendo 66,9% e 77,8% respectivamente. Conclusão: O trabalho em turno afeta a qualidade e as horas de sono, consequentemente altera o ritmo circadiano e hábitos alimentares devido à alteração da rotina das trabalhadoras. Sugere-se ações de educação em saúde a fim de tornar compatível o trabalho em turno com a qualidade de vida. [resumo fornecido pelo autor]
Keywords: Sono - Qualidade - Mulheres; Trabalho - Mulheres; Hábitos alimentares; Comportamento alimentar